New Insights into the Role of Sex Steroid Hormones in Pregnancy: Possible Therapeutic Approach by Sex Steroid Hormones for the Treatment of Both Preeclampsia and Preterm Labor - Mizutani, S.; Mizutani, E. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Fetal peptide hormones are essential for the development of fetus, which increase in accordance with pregnancy term. Concentration of these hormones within the feto-placental unit is normally higher than that of maternal circulation. Since these hormones are biologically active, the leakage of these hormones into the maternal circulation is regulated by degradation activity by placental aminopeptidases, in order to maintain the balance between carriage of pregnancy and onset of labor.Because the concentration of these hormones, being regulated by the amount of endogenous production and by physiological degradation by enzymes in the blood and tissue, the balance between production and degradation is a definitive element for maintaining normal gestation and term delivery.The changes of the balance between fetal angiotensin II (A-II) and vasopressin (AVP) andA-II and AVP degrading enzymes, between aminopeptidase A (APA) and placental leucine aminopeptidase( P-LAP) – in the placenta and maternal blood due to fetal stress such as hypoxia – are the provable causes of preeclampsia or preterm labor.Induction of APA and P-LAP by estradiol benzoate (E2) and progesterone (P) from placenta has been demonstrated. They are involved in the regulation of fetal peptide hormones via placental aminopeptidases in homeostasis of pregnancy.Recently it was shown that both APA and P-LAP could be potentially safe and effective drugs for preeclampsia and preterm labor. The authors’ proposed sex steroid treatment with dose increasing manner by gestational week (sex steroid treatment) for severe preeclampsia and preterm labor could be candidates replacing conventional treatments. In light of lacking safe and effective medication, the proposed sex steroid treatment is worthwhile for the prospective controlled studies for the treatment of both preeclampsia and preterm labor.
Keywords: preeclampsia; preterm labor; sex steroid treatment; new role of sex steroid hormones in pregnancy